The Trump phenomenon : how the politics of populism won in 2016 - Kivisto, Peter, 1948- (Emerald Publishing, 2017)
On November 8, 2016, American voters elected Donald J. Trump to become the 45th President of the United States. Peter Kivisto analyses how this happened, focusing on who Trump is, who his supporters are, and the role of the media, right-wing Christians and the Republican Party in making Trump's victory possible. The book concludes with an analysis.
Keywords: Trump, Donald, -- 1946-; Republican Party (U.S. : 1854- ); Presidents -- United States -- Election -- 2016.; Right and left (Political science) -- United States.; Political culture -- United States.; United States -- Politics and government -- 2009-; United States -- Social conditions -- 21st century.; United States.; Since 2000; elektronické knihy; electronic books